Sánchez-Mosquera, Marcial; Gutiérrez González, Pablo (eds.) (2023) Mercados de trabajo e instituciones en el sur de Europa. Madrid: Silex Universidad, 380 páginas - Martín Artiles, Antonio (Cuadernos de Relaciones Laborales, 2024)
The economic crisis of 2008 and the Great Recession highlighted the structural dysfunctions of the labor market in southern European countries, which particularly affects women and young people. It is a work history book, useful for research and teaching. Despite the fact that the interpretation of the crisis and the reforms do not have an unequivocal explanation, it is useful to analyze analyzes that consider the historical perspective, the common regulatory features and the differences between the three countries studied: Spain, France and Italy.